Policy Directions of Geothermal Potential at Sembalun District of East Lombok Regency in Nusa Tenggara Barat Province, Indonesia - Prana, Antoni Wira (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This research attempted to study physical characteristics of geothermal and formulate policy directions of geothermal potential through the process of ISM (Interpretative Structural Modelling) analysis in Sembalun District of East Lombok Regency. This descriptive qualitative research design used observation, interview, and documentation for collecting the data. Two types of data were collected, namely primary and secondary data. The result of ISM analysis on the data found that the geology of Sembalun area is the remains of an old volcano which has gone through destruction process with today’s remains’ characteristics of rough, rocky and steep ground surface and 550-2250 masl height. The geomorphology of Sembalun is classified into three units, namely morphology of steep volcano, morphology of sloping volcanic hills, and morphology of denudational plains. Sloping volcanic hills stretch from the northwestern to the southwestern areas and some in the southeastern area as a part of protected forest and national park of Mount Rinjani. The slope is between 30-70 degrees and arranged by volcanic rocks. Policy directions of geothermal potential are 1) as geothermal power plants for power sources, 2) geothermal energy for crop drying, 3) geothermal energy for sterilization of planting media in the future, and 4) geothermal energy for tourism sector.